RECOMMENDATIONS FOR LOCAL BUSINESSES BASED ON THE “NUDGE” APPROACH - Begimkulova Gulhayo Bakhtiyorovna (Western European Studies, 2025)
The “Nudge” strategy, which analyzes the effectiveness of local businesses, directs human behavior through soft nudges, while maintaining freedom of choice, urging customers to make the right decisions. For local businesses (small shops, cafes, service centers), this approach is important as a low-cost marketing and sales growth tool. The article presents the principles of “nudge”[1], international experience, social cues and visual nudges, as well as recommendations for their implementation in the context of local business. As a result of the study, the choice architecture, standard options and social proof significantly change customer behavior, increase sales and strengthen customer loyalty
Keywords: Nudge; choice architecture; local business